INFLUENCE OF SILICON-BASED COMPOSITE MATERIALS ON SOME THERMOELECTRIC PROPERTIES - Khojimatov, Islombek Turgʻunboy oʻgʻli (Innovative Development in Educational Activities, 2023)
In recent years, silicon and its based thermoelectric (TE) materials have attracted attention due to the advantages of low toxicity, low production costs and high stability. In this article, we review recent advances in the synthesis and characterization of silicon-based thermoelectric materials. In the first part of the article, it is shown that a large amount of silicon synthesized by natural nanostructure method, which is one of the new methods, exhibits a very high thermoelectric value of 0.6 zT at 1050 K temperature. In the second part, we consider the synthesis and characterization of Si nanocomposites and silicon-based thermoelectric materials. All of them are synthesized by the melt-spinning technique, which has rapid solidification properties. By this condition, it can be considered that the silicide precipitates are homogeneously distributed in the silicon matrix at any nanoscale size. And in the final part, we show promising new silicon-based thermoelectric composites for general thermo electrics, which exhibit very high power factor even at room temperature.